Generation of a Chimeric Hepatitis C Replicon Encoding a Genotype-6a NS3 Protease and Assessment of Boceprevir (SCH503034) Sensitivity and Drug-Associated Mutations. Issue 3 (April 2015) - Aloia, Amanda L; Eyre, Nicholas S; Black, Stuart; Bent, Stephen J; Gaeguta, Adriana; Guo, Zhuyan; Narayana, Sumudu K; Chase, Robert; Locarnini, Stephen; Carr, Jill M; Howe, John A; Beard, Michael R
Background: Genotype (gt)6 HCV is common amongst HCV-positive populations of the Asia–Pacific region but cell culture models for this gt have only recently been developed. Boceprevir (SCH503034) is a clinically available inhibitor of the HCV NS3 protein. We investigated the efficacy of boceprevir for inhibiting replication of a chimeric gt1b replicon encoding a gt6a NS3 protease and defined the development of mutations in the protease when boceprevir treatment was applied. Methods: We constructed a chimeric gt1b subgenomic replicon encoding a gt6 NS3 protease (NS3p) sequence (gt6NS3p_gt1b). The boceprevir EC50 value against replication of this replicon was determined using quantitative reverse transcriptase PCR. Next-generation sequencing was used to identify nucleotide changes associated with boceprevir resistance. The replication capacities of chimeric replicons containing mutations associated with boceprevir resistance were determined by colony formation efficiency assays. Results: The boceprevir EC50 value for the gt6NS3p_gt1b replicon was 535 ±79 nM. Boceprevir-resistant gt6NS3p_gt1b replicon cell lines could be selected and they demonstrated drug-associated amino acid changes that have previously been reported in other HCV gts. Interestingly, no mutations were observed at A156, a position defined for boceprevir resistance in gt1 NS3p, while mutation at N122, which is rarely reported in boceprevir-resistant gt1 proteases, was frequently observed. Re-introduction of these mutations into the chimeric replicon altered their replication capacity, ranging from complete abolishment of replication (A156T) to increasing replication capacity (V36A, N122S). This report provides the first characterization of gt6 HCV resistance to boceprevir. Conclusions: A chimeric HCV replicon encoding gt6 NS3 protease is sensitive to boceprevir and develops drug-resistant mutations at amino acid sites previously reported for other gts. Mutation at N122 also appears to be associated with boceprevir resistance in the gt6 NS3 protease.